Submandibular gland sialolith of unusual size - Kandel, Santosh; Pandey, Bhuwan Raj; Poudel, Prakash (Journal of Lumbini Medical College, 2017)
Introduction: Sialolithiasis is the most common disease of the salivary glands. Majority of sialoliths occur in the submandibular gland and is a common cause of acute and chronic infections of the gland. The size varies from one mm to one cm. Size greater than 15 mm are considered unusual or giant sialolith.Case report: We present a case of an unusual size sialolith of 16 mm in submandibular gland duct which was removed via transoral incision. The aim of presenting this case report is to understand etio-pathogenesis, clinical presentation and management of submandibular sialolithiasis.Conclusion:  Submandicular sialolithiasis of more than 15 mm in size though rare are not uncommon. They can be managed intraorally if situated at or near the orifice.